Does Medicaid Insurance Confer Adequate Access to Adult Orthopaedic Care in the Era of the Patient Protection and Affordable Care Act?. Issue 6 (June 2017) - Labrum, Joseph T.; Paziuk, Taylor; Rihn, Theresa C.; Hilibrand, Alan S.; Vaccaro, Alexander R.; Maltenfort, Mitchell G.; Rihn, Jeffrey A.
Abstract: Background: A current appraisal of access to orthopaedic care for the adult patient receiving Medicaid is important, since Medicaid expansion was written into law by the Patient Protection and Affordable Care Act (PPACA). Questions/Purposes: (1) Do orthopaedic practices provide varying access to orthopaedic care for simulated patients with Medicaid insurance versus private insurance in a blinded survey? (2) What are the surveyed state‐by‐state Medicaid acceptance rates for adult orthopaedic practices in the current era of Medicaid expansion set forth by the PPACA? (3) Do surveyed rates of access to orthopaedic care in the adult patient population vary across practice setting (private vs academic) or vary with different Medicaid physician reimbursement rates? (4) Are there differences in the surveyed Medicaid acceptance rates for adult orthopaedic practices in states that have expanded Medicaid coverage versus states that have foregone expansion? Methods: Simulated Patient Survey: We performed a telephone survey study of orthopaedic offices in four states with Medicaid expansion. In the survey, the caller assumed a fictitious identity as a 38‐year‐old male who experienced an ankle fracture 1 day before calling, and attempted to secure an appointment within 2 weeks. During initial contact, the fictitious patient reported Medicaid insurance status. One month later, the fictitious patient contacted the same orthopaedic practice and reported private insurance coverage status. National Orthopaedic Survey: Private and academic orthopaedic practices operating in each state in the United States were called and asked to complete a survey assessing their practice model of Medicaid insurance acceptance. State reimbursement rates for three different Current Procedural Terminology (CPT ®) codes were collected from state Medicaid agencies. Results Simulated Patient Survey: Offices were less likely to accept Medicaid than commercial insurance (30 of 64 [47%] versus 62 of 64 [97%]; odds ratio [OR], 0.0145; 95% CI, 0.00088‐0.23639; p < 0.001), and patients with Medicaid were less likely to be offered an appointment within 2 weeks (23 of 64 [36%] versus 59 of 64 [89%]; OR, 0.0154; 95% CI, 0.00094‐ 0.251; p < 0.001). The Medicaid acceptance rates observed across states sampled in the simulated patient survey were 67% (Pennsylvania), 21% (New Jersey), 58% (Delaware), and 50% (Maryland) (p = 0.04). National Orthopaedic Survey: Adult patients with Medicaid insurance had limited access to care in 109 of 342 (32%) orthopaedic practices: 37% of private and 13% of academic practices (p < 0.001). Practices that accepted Medicaid received higher reimbursement for each CPT ® code relative to those that did not and acceptance of Medicaid became increasingly more likely as reimbursement rates increased (99243: OR, 1.03, 95% CI, 1.02‐1.04 per dollar, p < 0.001; 99213: OR, 1.05; 95% CI, 1.03‐1.07 per dollar, p < 0.001; 28876: OR, 1.01, 95% CI, 1.00‐1.01 per dollar, p < 0.001). For a given reimbursement rate, private practices were less likely to take an adult patient with Medicaid relative to an academic practice (99243: OR, 0.11, 95% CI, 0.04‐0.33, p < 0.001; 99213: OR, 0.11, 95% CI, 0.04‐0.32, p < 0.001; 27786: OR, 0.12, 95% CI, 0.04‐0.35, p < 0.001). No difference was observed when comparing Medicaid acceptance rates for all practice types between states that have expanded their Medicaid program versus those that have not (OR, 1.02; 95% CI 0.62‐1.70; p = 0.934). Conclusions: In this two‐part survey study, we found that a simulated patient with commercial insurance was more likely to have their insurance accepted and to gain timely access to orthopaedic care than a patient with Medicaid. Academic practice setting and increased Medicaid reimbursement rates were associated with increased access to care for the patient with Medicaid. Inequality in access to orthopaedic care based on health insurance status likely exists for the adult patient with Medicaid. Furthermore, Medicaid expansion has likely realized minimal gains in access to care for the adult orthopaedic patient. Further research is needed in delineating the patient‐payer selection criteria used by orthopaedic practices to aid policymakers in reforming the Medicaid program and comprehensibly addressing this access to care disparity. Level of Evidence: Level II, prognostic study.